2022
DOI: 10.1186/s43166-022-00119-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of estrogen receptor alpha gene (ESR1) polymorphism and its relation to systemic lupus erythematosus disease status

Abstract: Background Systemic lupus erythematosus (SLE) is a chronic inflammatory disease with variable clinical manifestations that can affect various organs and tissues. Estrogen is an important element that performs a vital role in the pathology of SLE. It acts on target cells through binding to estrogen receptors (ERs). This study aimed to assess the effect of ER alpha gene polymorphism on SLE disease activity and clinical manifestations. This study included 30 SLE female patients and 20 healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to the studies, several gene polymorphisms of NR have been found to be associated with diverse diseases [25][26][27] . Homodimeric receptor ERα harbouring SNPs (rs2234693) is a pathogenic factor for Systemic Lupus Erythematosus (SLE) disease severity 28 . Similarly, polymorphism in other NRs, such as Heterodimeric receptor THR and orphan receptor HNF-4α, are reported in the risk of hypertension/ systolic BP and Crohn's disease, respectively [29][30] .…”
Section: Snp Variants Of Vdr and Disease Associationmentioning
confidence: 99%
“…According to the studies, several gene polymorphisms of NR have been found to be associated with diverse diseases [25][26][27] . Homodimeric receptor ERα harbouring SNPs (rs2234693) is a pathogenic factor for Systemic Lupus Erythematosus (SLE) disease severity 28 . Similarly, polymorphism in other NRs, such as Heterodimeric receptor THR and orphan receptor HNF-4α, are reported in the risk of hypertension/ systolic BP and Crohn's disease, respectively [29][30] .…”
Section: Snp Variants Of Vdr and Disease Associationmentioning
confidence: 99%